KAJIAN DERAJAT PELAPUKAN BATUAN DAN IMPLIKASINYA TERHADAP KLASIFIKASI MASSA BATUAN ROCK MASS RATTING DI DAERAH BENDUNGAN BAWAH CISOKAN - Muhadi, Ulfi
Rock weathering is a transformative process af ecting rocks on the Earth's surface due to physical, chemical, and biological factors. This weathering can alter the strength of rocks by more than 50% from their original strength, and at the highest degree, it can transform rocks into soil. The research is conducted at the Lower Cisokan Dam, West Bandung Regency, West Java Province, on volcanic rock formations and sedimentary rock formations. The research site is located along the access road with a total of 12 observation stations (STA). Data is collected using a Schmidt hammer, scanline, and field observations at each STA. The data is processed graphically to illustrate changes in graphical patterns and analyzed using arithmetic methods. The results of the analysis are then compared with various previous studies for validation testing. This research discusses parameters influencing changes in the Rock Mass Rating (RMR) based on dif erent levels of rock weathering. The degrees of rock weathering are categorized into 4 levels: fresh (I), slightly weathered (II), moderately weathered (III), and highly weathered (IV). Evaluation of the analysis results is conducted based on RMR parameters and field observations. The research indicates that parameters undergoing changes due to the degree of rock weathering include UCS, aperture, roughness, and infilling. The implications of changes in RMR parameter values result in alterations of up to 13% from the RMR value before undergoing the weathering process. These changes can further impact engineering activities to be conducted at the research site